Impact of Wheat/Faba Bean Mixed Cropping or Rotation Systems on Soil Microbial Functionalities - Wahbi, Sanâa; Prin, Yves; Thioulouse, Jean; Sanguin, Hervé; Baudoin, Ezékiel; Maghraoui, Tasnime; Oufdou, Khalid; Le Roux, Christine; Galiana, Antoine; Hafidi, Mohamed; Duponnois, Robin (Frontiers in Plant Science, 2016)
Cropping systems based on carefully designed species mixtures reveal many potential advantages in terms of enhancing crop productivity, reducing pest and diseases and enhacing ecological serices. Associating cereals and legume production either through intercropping or rotations might be a relevant strategy of producing both type of culture, while benefiting from combined nitrogen fixed by the legume through its symbiotic association with nitrogen-fixing bacteria, and from a better use of P and water through mycorrhizal associations. These practices also participate to the diversification of agricultural productions, enabling to secure the regularity of income returns across the seasonal and climatic uncertainties. In this context, we designed a field experiment aiming to estimate the two years impact of these practices on wheat yield and on soil microbial activities as estimated through Substrate Induced Respiration (SIR) method and mycorrhizal soil infectivity (MSI) measurement. It is expected that understanding soil microbial functionalities in response to these agricultural practices might allows to target the best type of combination, in regard to crop productivity. We found that the tested cropping systems largely impacted soil microbial functionalities and mycorrhizal soil infectivity. Intercropping gave better results in terms of crop productivity than the rotation practice after 2 cropping seasons. Benefits resulting from intercrop should be highly linked with changes recorded on soil microbial functionalities.